Seite eines Albums, in dem Zeitungsartikel über das Iwalewahaus aufgeklebt sind und Fotografien der Veranstaltungen - Beier, Ulli (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Art; Painting; Africa; Exhibitions; Photographs; Newspapers; Albums; Art Exhibition; Newspaper Article; Iwalewahaus; Cultural Centre; Performing Arts Center